Toxicity studies of p-toluenesulfonamide administered in feed to F344/N rats, F344/NTac rats, and B6C3F1/N mice. (Toxic Rep Ser, 2016)
p-Toluenesulfonamide is formed from chloramine-T, an antimicrobial agent used by the aquaculture industry to treat fish intended for human consumption. Chloramine-T is also widely used as a disinfectant in the medical, dental, veterinary, food processing, and agricultural industries. Because of its low degree of cytotoxicity, chloramine-T has been used in direct contact with tissues, including treatment for burns, in whirlpools for wounds, and as an oral mouthwash. In the agricultural industry, it is used as a broad-spectrum biocide for foot-and-mouth disease, swine vesicular disease, and poultry diseases. Chloramine-T was nominated by a private individual for toxicology studies based on its current status as an Investigational New Animal Drug for controlling proliferative gill disease and bacterial gill disease in aquaculture and the need for additional toxicology studies to support its safe use. p-Toluenesulfonamide was studied for toxicity by the NTP because it has been shown to be the major product formed from chloramine-T. For the 2-week studies, male and female F344/N rats and B6C3F1/N mice were exposed to p-toluenesulfonamide (greater than 99% pure) in feed. For the 3-month studies, male and female F344/NTac rats and B6C3F1/N mice were exposed to p-toluenesulfonamide (greater than 99% pure) in feed. Genetic toxicology studies were conducted in Salmonella typhimurium, rat peripheral blood erythrocytes, and mouse peripheral blood erythrocytes. (Abstract Abridged).